2021
DOI: 10.1002/anie.202110351
|View full text |Cite
|
Sign up to set email alerts
|

A Biocatalytic Cascade in an Ultrastable Mesoporous Hydrogen‐Bonded Organic Framework for Point‐of‐Care Biosensing

Abstract: Herein, we report the first example of using mesoporous hydrogen‐bonded organic frameworks (MHOFs) as the protecting scaffold to organize a biocatalytic cascade. The confined microenvironment of MHOFs has robust and large transport channels, allowing the efficient transport of a wide range of biocatalytic substrates. This new MHOF‐confined cascade system shows superior activity, extended scope of catalytic substrates, and ultrahigh stability that enables the operation of complex chemical transformations in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 46 publications
4
82
0
5
Order By: Relevance
“… [41] This idea is in good agreement with examples of HOF composites that report superior Y P for amino‐modified model proteins (i. e., BSA and GFP), compared with pristine and carboxyl‐modified proteins. [ 41 , 67 ] The structures of the DAAO biocomposites were examined by X‐ray diffraction (XRD), which revealed that the diffraction patterns of DAAO@BioHOF‐1 and Z‐DAAO@BioHOF‐1 were analogous to that of as‐synthesized BioHOF‐1 (see Figure S9 and Figure 3 a). [40] …”
Section: Resultsmentioning
confidence: 99%
“… [41] This idea is in good agreement with examples of HOF composites that report superior Y P for amino‐modified model proteins (i. e., BSA and GFP), compared with pristine and carboxyl‐modified proteins. [ 41 , 67 ] The structures of the DAAO biocomposites were examined by X‐ray diffraction (XRD), which revealed that the diffraction patterns of DAAO@BioHOF‐1 and Z‐DAAO@BioHOF‐1 were analogous to that of as‐synthesized BioHOF‐1 (see Figure S9 and Figure 3 a). [40] …”
Section: Resultsmentioning
confidence: 99%
“…D) Structural illustration of the HOFs cascades nanoreactor. Reproduced with permission [5c] . Copyright 2021, Wiley‐VCH.…”
Section: Multienzyme Immobilization Utilizing Pofs Hostmentioning
confidence: 99%
“…1D). Since the well‐arranged mesoporous channels of HOFs enabled the accessibility of the guests that have a wide range of molecular dimensions, the HOFs‐MBCS allowed operating versatile cascade process that had previously not been explored in micropore ZIFs counterparts [5c] …”
Section: Multienzyme Immobilization Utilizing Pofs Hostmentioning
confidence: 99%
See 2 more Smart Citations